Penerapan Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) Dalam Meningkatkan Kemahiran Membaca Bahasa Arab di Madrasah Aliyah - Udhia, Inayatul; Erlina, Erlina; Basyori, Ahmad; Koderi, Koderi (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2024)
ملخص: أجري هذا البحث لتحليل تطبيق نموذج التعلم التعاوني المتكامل في القراءة والتعبير (CIRC) في تحسين مهارات القراءة باللغة العربية باستخدام الوسائط القائمة على برنامج Power Point لدى طلاب الصف الحادي عشر IPS 2 في المدرسة العالية معارف كيبوتران برينغسيوو. الهدف من هذا البحث هو وصف تطبيق وفعالية نموذج التعلم التعاوني المتكامل في القراءة والتعبير (CIRC) في تعلم اللغة العربية. هذا البحث هو بحث إجرائي في الفصل الدراسي (Classroom Action Research) مع منهج نوعي. بناءً على التحليل الذي تم إجراؤه، تظهر نتائج البحث أن تعلم اللغة العربية باستخدام نموذج التعلم التعاوني المتكامل في القراءة والتعبير (CIRC) يمكن أن يحسن مهارات القراءة لدى الطلاب. ويمكن ملاحظة ذلك من خلال التحصيل التعليمي الذي ارتفع إلى 77.6% في الدورة الأولى و88.8% في الدورة الثانية. بالإضافة إلى ذلك، زاد الحماس لتعلم اللغة العربية وتزايد تعاون الطلاب والتفكير النقدي. الكلمات الرئيسية: اللغة العربية، CIRC، مهارة القراءة Abstract: This study aimed to examine the implementation of the Cooperative Integrated Reading and Composition (CIRC) learning model in enhancing Arabic reading skills among students of class XI IPS 2 at senior high school Ma'arif Keputran Pringsewu, utilizing PowerPoint-based media. The objective was to delineate the application and efficacy of the Cooperative Integrated Reading and Composition (CIRC) learning model in Arabic language instruction. Employing a qualitative approach, this research adopted a classroom action research (CAR) methodology. The analysis revealed that employing the Cooperative Integrated Reading and Composition (CIRC) model in Arabic language instruction resulted in improved reading skills among students. This improvement was evidenced by learning achievements, which increased to 77.6% in cycle 1 and further to 88.8% in cycle 2. Furthermore, there was an observed increase in students' enthusiasm for learning Arabic, collaboration, and critical thinking skills. Key words: Arabic, CIRC, reading skills Abstrak: Penelitian ini dilakukan untuk menganalisis penerapan model pembelajaran Cooperative Integrated Reading and Composition (CIRC) dalam meningkatkan kemahiran membaca bahasa Arab dengan menggunakan media berbasis power point pada siswa kelas XI IPS 2 MA Ma’arif Keputran Pringsewu. Adapun tujuan penelitian ini yaitu mendeskripsikan penerapan dan efektivitas model pembelajaran Cooperative Integrated Reading and Composition (CIRC) dalam pembelajaran bahasa Arab. Penelitian ini adalah penelitian tindakan kelas (Classroom Action Research) dengan pendekatan kualitatif. Berdasarkan analisis yang dilakukan, hasil penelitian menunjukkan bahwa pembelajaran bahasa Arab dengan model Cooperative Integrated Reading and Composition (CIRC) dapat meningkatkan keterampilan membaca siswa. Hal ini terlihat dari prestasi belajar yang meningkat menjadi 77,6% pada siklus 1 dan 88,8% pada siklus 2. Selain itu, semangat belajar bahasa Arab, kerjasama siswa dan berpikir kritis meningkat. Kata kunci: Bahasa Arab, CIRC, kemahiran membaca